An essential need: Creating opportunities for veterinary students and graduates to gain an appreciation of responsibilities and opportunities in global veterinary issues - Malone, J. B.; Bavia, M. E.; Stromberg, B. E.; Valadao, C. [UNESP]; Wiles, W. T.; Diaz, J. H.; Bergquist, R. (WOAH (World Organisation for Animal Health), 2009)
Globalisation trends and bioterrorism issues have led to new concerns relating to public health, animal health, international trade and food security. There is an imperative to internationalise and strengthen global public health capacity by renewed emphasis on veterinary public health in veterinary education and increasing opportunities for elective experiential learning in public practice programmes for veterinary students. Recent experience with a US-Brazil Higher Education Consortia Program is used as an example of potential ways in which veterinary students can gain an appreciation for global veterinary issues.
Keywords: Academic exchanges; Curriculum; Education; Geographic information systems; Globalisation; International veterinary medicine; Veterinary public health; Western hemisphere